Effect of gamma irradiation and frozen storage on the quality of fresh water prawn (Macrobrachium rosenbergii) and tiger prawn (Penaeus monodon). Issue 2 (May 2015) - Mahto, Rina; Ghosh, Sayanti; Das, Malay K.; Das, Madhusudan
Abstract The study was carried out on two important species of prawns (Macrobrachium rosenbergii and Penaeus monodon) aimed at understating the effect of increasing irradiation doses (0.5, 1.5, 2.5, 3, 5, 10 and 20 kGy) on their structural components studied by histology and x-ray diffraction and to determine the effect of irradiation and frozen storage on the mechanical properties (shear force, toughness and cohesiveness), visual appearance and microbiological quality (total bacterial count, mould count, coliform count and detection of Salmonella) of prawns during storage for 56 days. Low dose irradiation (≤10 kGy) induced no significant changes in microstructure and mechanical properties in fresh prawns. Structural changes became apparent at 20 kGy, although they failed to induce any significant effect on the muscle firmness, toughness and cohesiveness. Irradiation with 2.5 kGy and above reduced melanosis in both the species. Low dose irradiation (1.5–3 kGy) significantly reduced the total bacterial and mould counts and eliminated coliforms and Salmonella. Low dose irradiation (2.5–5 kGy) in combination with frozen storage effectively preserved the mechanical attributes, visual quality and improved the microbial safety of the prawns during long term storage. The technique could satisfy the increasing consumer demand for high quality, minimally processed, additive-free sea foods.